Playing it down - effectiveness of clay therapy, origami and building blocks in the management of dental anxiety among children aged 6-10 years - Srinivasan, Smrithi; Gowda, Laghna; Srinivasan, Ila; Haridasan, Ajith Kumar; Yajaman, Shilpa Sheshadri (International Journal of Contemporary Pediatrics, 2023)
Background: Children experience dental anxiety during their first dental visit, which affects the quality of dental treatment and gives rise to behaviour management problems. Clay, origami and building blocks have been effective in alleviating hospitalization anxiety in pediatric patients. These successful techniques in hospitalized pediatric patients have seldom been used in the dental set up. Therefore, the aim of this study is to assess and compare the efficacy of clay therapy, origami and building blocks in the management of dental anxiety in children aged 6-10 years. Methods: Sixty children aged 6-10 years, with no previous dentist exposure, with Frankl’s behaviour rating 2 or 3 having dental caries with international caries detection and assessment system (ICDAS) score 3 requiring restorations without local anesthesia were selected and divided into four groups. Group 1 – clay therapy; group 2 - building blocks; group 3 – origami; and group 4 – tell show do. Pulse rate, facial image scale (FIS) and face, leg, activity, cry, consolability (FLACC) behaviour scales were used to quantify anxious behaviour. Operator compliance and parent acceptance was rated on the Likert scale. Results: The results showed lower mean pulse rates, lower FIS and FLACC scores, and better operator compliance and parental acceptance in clay therapy, origami and building blocks groups than in the conventional tell-show-do group. The most significant reduction in all the parameters was seen in the clay therapy group. Conclusions: Clay therapy, origami and building blocks can be used as an effective means to reduce dental anxiety in children.